Effective Partnership between Business and Business for Shared Value - Mori, Yusuke (2014)
Objective of this report is to analyse how global business can create shared values from business-to-business partnership. Porter and Kramer (2011) introduce shared value defined as creating simultaneous economic and social benefits, and can enhance competitive advantage of the company by addressing its needs and challenges. There are various types of business partnerships. In this report, I analyse motivations of and benefits to corporate and its partner, challenges and pros and cons of partnership to understand effective business-to-business partnership for shared value. Firstly, I introduce literature review related to corporate partnership to understand types of partnerships, motivations, benefits, factors of effective partnership etc. Secondly, I explain method of the report based on literature review. Thirdly, I take up three partnerships and analyse them to understand effective partnership. I start from introduction of general information of four organisations which participate in three partnerships to understand the background of partnerships. Then, I analyse each partnership. Fourthly, I illustrate my findings based on the analysis of three partnerships. Lastly, I conclude the analysis and suggest future research agenda.